Modernist muslims and some contemporary reforms in muslim law in the middle east: an appraisal (2015)
This paper examines the reforms introduced into marriage, divorce and inheritance in Islam by modernist Muslims. It traces the origin of the reforms and demonstrates that their reforms are nothing but deviations from the Shariah. It submits that while Islam allows limited polygamy (polygyny) against the stand of modernist Muslims which considers polygamy impracticable, the religion however places some restrictions. We have also shown in this article that it is better to bring a marriage to a peaceful end rather than making the couple and the children live in “hell” indefinitely against the stand of modernist Muslims who made divorce extremely difficult and practically impossible because of the conditions attached to it. The paper argues that giving orphans and grandchildren obligatory bequest when the children are in existence as advocated by modernist Muslims is not Shariah compliant.